Endoscopic treatment of bile duct post-traumatic and post-operative lesions in children. (3rd August 2017) - Keil, Radan; Drabek, Jiri; Lochmannova, Jindra; Stovicek, Jan; Rygl, Michal; Snajdauf, Jiri; Hlava, Stepan
Abstract: Background and study aims: The aim of this study was to assess the significance and safety of endoscopic retrograde cholangiopancreatography (ERCP) in diagnosing and treating bile duct injuries in children. Patients and methods: Fourteen pediatric patients, with traumatic or postoperative bile duct injury, in which ERCP was performed, were retrospectively evaluated. Results: We performed 46 ERCP and 12 endoscopic papillotomies in children with suspected bile duct injuries. A bile stent was primarily inserted in 13 patients and there were 20 replacements. Endoscopic treatment of bile leakage without need for bile duct sutures or reconstruction was successful in 85.7%. Post ERCP complications included cholangitis and recurrent bleeding, which occurred only in two patients each. Conclusions: ERCP and endoscopic bile stent insertion is a highly effective, minimally-invasive treatment for bile duct injury and should be included as part of the therapeutic procedures in pediatric patients with suspected bile duct injury.